Keramahtamahan: Apakah Berpengaruh Terhadap Independensi Auditor? - Setiawan, Nanang; Wahyudi, Imam (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2022)
This study analyzing aspects of hospitality to auditors and how it affects audit independence and quality of audit results. This study uses a descriptive qualitative method and a literature study approach to provide adequate understanding and explanation of a topic obtained from various literature sources. The hospitality regardless of the amount, even if the amount is below the materiality limit (KPK, 2020) may not affect the audit results. Gifts and hospitality will affect their credibility and independence as an auditor (Kampai, 2020) and the auditor independence has a positive effect on audit quality audit (DeAngelo, 1981; Megayani et al., 2020; Samsi et al., 2013; Santoso & Riharjo, 2020; Wardhani et al., 2015). This study contributes to filling the gap in previous research because there has been no similar study focuses hospitality towards independence and the quality of audit results